PELATIHAN VIDEO PEMBELAJARAN BERBASIS MULTIMEDIA POWTOON DAN MEDIA UJIAN ONLINE GOOGLE FORMS UNTUK PENUNJANG PELAKSANAAN PEMBELAJARAN ONLINE DI SMPN 1 ANJIR PASAR - Erfan Karyadiputra; Sefto Pratama; Agus Alim Muin (JURNAL PENGABDIAN AL-IKHLAS UNIVERSITAS ISLAM KALIMANTAN MUHAMMAD ARSYAD AL BANJARY, 2021)
The Covid-19 pandemic indirectly impacted the transformation of the education system that was once the learning process is still conducted face-to-face, when the pandemic began to be directed into online learning. Community Service aims to help partners, namely SMPN 1 Anjir Pasar who are still having difficulty in utilizing information and communication technology facilities, especially in the online learning process during the Covid-19 pandemic. The priority of partner problems is divided into two parts, namely the first is still a lack of skills in the creation of multimedia-based learning media such as Powtoon so that learning seems monotonous. The second problem is the lack of skills in utilizing Google Forms media as an online test media because it is only limited to using WhatsApp media which of course uses it less efficiently to be used as an online exam medium. With the community service activities to SMPN 1 Anjir Pasar, of course, the hope is to help teachers in understanding and utilizing information and communication technology facilities well and able to use the information technology facilities as a means of supporting media in the implementation of online learning during the Covid-19 pandemic.